A collaborative approach to graduate preparation in higher institutions for global economy in Nigeria (2014)
As the world becomes a global village, one expects that a young graduate will, exhibits, integrate and apply the knowledge-of technology effectively to solve societal problems. Barents, employers, and people at the corridor of power are interested in the quality of output provided by the universities. All of these expectations fall short in the quality of graduates that are- turned out in Nigeria. Institutional -leaders who hire hew graduates for various positions, 'analysts of higher education, and potential administrative staff raise questions about the appropriateness of graduate preparation for the changing workplace contexts. Without doubt, individuals expected to replace retiring workforce must demonstrate a wider array of talents than their predecessors, as well as higher levels of productivity. In this context, the experiences of these new graduates are characterized by stress, pressure, inefficiency ineffectiveness and uncertainty that made them unfit for the work available. It is therefore the aim. of this paper to address the question of whether or not the graduate preparation process is adequate and appropriate, and whether there will be provision of industrious and efficient graduates if higher institutions collaborate with community. The study is a survey type. A multistage sampling technique was used to select fifteen universities and three hundred participants. One instrument, Graduate Preparation Process Questionnaire (GPPQ) was administered to collect data from participants. The result revealed that 87% agreed that the learning period is adequate for producing quality, graduates. Moreover, 92% agreed that the curriculum is long overdue for review while majority of the participants 86% agreed that the academic environment is not conducive for learning. Lastly, 64% agreed that collaborative efforts with communities will bring about provision of quality graduates. It is recommended that innovative approach by higher institutions should be implemented to remove barriers to academic excellence and demonstration of skills sufficient enough for engagement in labour market.